Distance on the Yo-Yo Intermittent Recovery Test is associated with Flow- Mediated Dilatation in young soccer players - Walter Oliveira de Vargas; Katya Vianna Rigatto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2018)
The Yo-Yo intermittent recovery test evaluates the individual capacity to carry out intermittent exercise leading to a maximal activation of the aerobic system. It has also been shown that aerobic exercise improves endothelial function (FMD). Moreover, studies indicate that there is a positive association between FMD and maximal oxygen uptake, but no data is available about the association with the Yo-Yo intermittent recovery test. Thus, the aim of the present study was to investigate, in young football players, whether the Yo-Yo intermittent recovery test level 1 could also be associated to the FMD. Thirteen young male football players (athletes) and eleven young male non-athletes (control) participated in this study. The FMD and Yo-Yo intermittent recovery test level 1 were measured in each group. FMD and the distance on Yo-Yo intermittent recovery test level 1 were significantly higher (P<0.002 and P<0.001, respectively) in the athletes (FMD=11.5±3.8; Yo-YoIR1= 2009.2 ± 263.8) than in control group (FMD=4.9 ± 5.4; Yo-YoIR1= 1420 ± 423.8). The Pearson correlation between FMD and the distance on the Yo-Yo intermittent recovery test level 1 in the athletes group was r = 0.81 (P<0.005), while in the control group it was r = 0.03 (P<0.005). Our results indicate that there is a positive association between Yo-Yo intermittent recovery test level 1 and FMD in young football players. This association strengthens the Yo-Yo intermittent recovery test level 1 as an effective tool in evaluating the performance of intermittent sports athletes.   RESUMO  Distância no Yo-Yo Intermittent Recovery Test está associada com a Dilatação Mediada por Fluxo em jovens jogadores de futebol O Yo-Yo Intermittent Recovery Test avalia a capacidade individual para realizar exercício intermitente levando a uma ativação máxima do sistema aeróbio. Também foi demonstrado que o exercício aeróbio melhora a função endothelial (FMD). Além disso, estudos indicam que existe uma associação positiva entre a FMD e o consume máximo de oxigênio, mas não há dados disponíveis sobre a associação com o Yo-Yo Intermittent Recovery Test. Assim, o objetivo do presente estudo foi investigar, em jovens jogadores de futebol, se o Yo-Yo Intermittent Recovery Test nível 1 poderia também estar associado à FMD. Treze jovens jogadores de futebol (atletas) e onze jovens não-atletas (controle) participaram deste estudo. A FMD e o Yo-Yo Intermittent Recovery Test nível 1 foram medidos em cada grupo. A FMD e a distância no Yo-Yo Intermittent Recovery Test nível 1 foram significativamente maiores (P <0,002 e P <0,001, respectivamente) nos atletas (FMD = 11,5 ± 3,8; Yo-YoIR1 = 2009,2 ± 263,8) que no grupo controle (FMD = 4,9 ± 5,4, Yo-YoIR1 = 1420 ± 423,8). A correlação de Pearson entre a FMD e a distância no Yo-Yo Intermittent Recovery Test nível 1 no grupo atletas foi r = 0,81 (P <0,005), enquanto no grupo controle foi r = 0,03 (P <0,005). Nossos resultados indicam que há uma associação positiva entre o Yo-Yo Intermittent Recovery Test nível 1 e a FMD em jovens jogadores de futebol. Esta associação fortalece o Yo-Yo Intermittent Recovery Test nível 1 como uma ferramenta eficaz na avaliação do desempenho de atletas de esportes intermitentes.